Thinking without knowing: Psychological and behavioral consequences of unjustified confidence regarding blackjack strategy - Stone, Eric R.; Parker, Andrew M.; Hanks, Ashley Rittmayer; Swiston, Robert C. (Frontiers in Psychology, 2023)
In two studies, we explored potential psychological and behavioral consequences of unjustified confidence, including outcome expectations, anxiety, risk taking, and information search and consideration. Study 1 employed an individual-differences approach to examine how participants’ confidence regarding their knowledge of blackjack strategy, controlling for their actual knowledge, correlated with these hypothesized psychological and behavioral variables. Study 2 manipulated participants’ confidence levels to examine these effects. Across the two studies, greater unjustified confidence led to larger bets (a measure of risk taking) and reduced use of hints designed to improve play (information search and consideration). Unjustified confidence also increased participants’ outcome expectations and lowered anxiety levels. Implications of these findings, such as for educational interventions, are discussed.